(x+4)((x^2) - kx - 5) is expanded and simplified. The coefficient of the x^2 term twice the coefficient of the x term. Work out the value of k.

(x + 4) (x2 - kx - 5) = x3 - kx2 - 5x + 4x2 - 4kx - 20 = x3 + (4-k)x2 + (-5-4k)x - 20.The coefficients are: (4-k) of x2 and (-5-4k) of x. Now we can write the equation:(4-k) = 2(-5 - 4k) /expand4 - k = -10 - 8k /+8k4 + 7k = -10 /-47k = -14 /divide by 7k = -2

Related Further Mathematics GCSE answers

All answers ▸

If y=(x^2)*(x-10), work out dy/dx


Use the factor theorem to show that (x-1) is a factor of x^3 - 3x^2 -13x + 15


What is the equation of a circle with centre (3,4) and radius 4?


A particle is moving in a straight line from A to B with constant acceleration 4m/s^2. The velocity of the particle at A is 3m/s in the direction AB. The velocity of the particle at B is 18m/s in the same direction/ Find the distance from A to B.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences